2019
DOI: 10.1177/1947603519888787
|View full text |Cite
|
Sign up to set email alerts
|

LINC01534 Promotes the Aberrant Metabolic Dysfunction and Inflammation in IL-1β-Simulated Osteoarthritic Chondrocytes by Targeting miR-140-5p

Abstract: Objective Long non-coding RNA 01534 (LINC01534) is highly expressed in the tissues of patients with osteoarthritis (OA). This study investigated the mechanism of LINC01534 on abnormal metabolic dysfunction in OA chondrocytes induced by interleukin-1β (IL-1β). Methods The quantitative real-time polymerase chain reaction (qRT-PCR) was used to determine the expressions of LINC01534, aggrecan, collagen II, and matrix metalloproteinase (MMPs) in OA cartilage tissue or OA chondrocyte model induced by IL-1β. The expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…HOTAIR is known as an oncogenic lncRNA in various type of human cancer. 8 However, the LINC01534 literature was limited solely to the inflammatory disease osteoarthritis 10 and we are not aware of any reports on LINC01534 in human cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOTAIR is known as an oncogenic lncRNA in various type of human cancer. 8 However, the LINC01534 literature was limited solely to the inflammatory disease osteoarthritis 10 and we are not aware of any reports on LINC01534 in human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated high expression of lncRNA 01534 (LINC01534) in the inflammatory disease osteoarthritis, and showed that LINC01534 promotes an inflammatory response through proinflammatory factors, such as TNF‐α and IL‐6 10 . To date, however, we are not aware of any reports that describe LINC01534 in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal chondrocyte metabolism is risk factor for OA and can have a direct systemic impact on the joints ( Zheng et al, 2021 ). In the OA setting, the main components of the ECM, aggrecan and type II collagen, are reduced due to inhibition of chondrocyte synthetic activity ( Wei et al, 2021 ). In OA cartilage, the rate of anaerobic glycolysis is increased and changes in key enzymes and glycolytic processes lead to the production and accumulation of excess lactic acid by chondrocytes, creating an acidic microenvironment ( Maneiro et al, 2003 ).…”
Section: Relationship Between Pgc-1α and Abnormal Metabolism Of Chond...mentioning
confidence: 99%
“…Long intergenic noncoding RNAs (lincRNAs) have also been involved in the onset and development of OA. In particular, LINC00265, LINC00461, LINC00473, LINC01534, and LINC02288 [ 62 , 63 , 64 , 65 , 66 ] have been demonstrated to promote inflammatory responses by sponging related miRNAs. Among these lincRNAs, LINC00265, LINC00473, and LINC02288 have also been shown to promote apoptosis.…”
Section: Regulatory Roles Of Lncrnas In Osteoarthritis Cartilagementioning
confidence: 99%